Factor associated with tobacco use among the adult population in Sarawak, Malaysia: a cross sectional study (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction: Consumption of tobacco in any form is one of the leading causes of preventable mortality. The World Health Organization recommends that it should be monitored regularly.  This study was designed to estimate the prevalence of tobacco use among the rural adult population in Sarawak and factors associated with it.Methods: This was a cross-sectional study conducted among the adult population in Sarawak. Data were collected from ten villages in Kota Samarahan and Kuching Division by face to face interview using modified Global Adult Tobacco Survey questionnaire. Non-probability sampling method was adopted to select the villages. All the households of the villages were visited and an adult member was selected randomly from each house irrespective of the sex. After missing value imputation, 1000 data were analysed using statistical software SPSS 19.0 version.Results: Analysis showed that 30.9% of the respondents were current tobacco users and 11% were past tobacco users. The mean age (SD) at starting tobacco was 18.1 (6.48) years. The frequency of tobacco use was 14 times per day.  Hierarchical Logistic regression analysis revealed that age with male sex (OR=1. 064, 95% CI: 1.052, 1.076), secondary education (OR=-2.712; 95% CI: 1.122, 6.555), higher secondary and above (OR=3. 571; 95% CI: 1.641,7.774), occupation as business (OR=3. 152; 95% CI: 1.732, 5.735) and environmental exposure such as smoking at working place (OR=2. 754;95% CI: 1.895,4.002), coffee house (OR=2. 274;95% CI: 1.32,3.919) and at home (OR=1. 827;95% CI: 1.242,2.687) appeared to be  important predictors of tobacco use (p
Keywords: Cigarettes; Environment; Prevalence; Tobacco; Sarawak